2022
DOI: 10.4018/ijsesd.292039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peer Influence and Environmental Knowledge on Green Consumption

Abstract: In current times, the concept of sustainable consumption is at the forefront owing to the impact it creates on the society and the environment. Consumers have become more observant towards the consumption related environmental problems and it influences their purchase decisions. There is a link between the consumer concern for the environment and also their knowledge levels about the environment friendly products. While most of the studies agree that environmental knowledge and environmental concern as the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Previous research has found that peer influence directly influences on adolescents' green buying behavior [81]. Again, Green involvement and purchasing are significantly influenced by social influence [82]. According to the social learning theory, individuals learn by seeing, imitating, and seeking advice from their peers, and so peers constitute a primary source of knowledge for consumers.…”
Section: Peer Influencementioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has found that peer influence directly influences on adolescents' green buying behavior [81]. Again, Green involvement and purchasing are significantly influenced by social influence [82]. According to the social learning theory, individuals learn by seeing, imitating, and seeking advice from their peers, and so peers constitute a primary source of knowledge for consumers.…”
Section: Peer Influencementioning
confidence: 99%
“…According to the social learning theory, individuals learn by seeing, imitating, and seeking advice from their peers, and so peers constitute a primary source of knowledge for consumers. Peer network supports green consciousness and behavior, including local environmental involvement and general green purchasing behavior [82]. Thus, customers' purchasing decisions are frequently influenced by coworkers, salesmen, and celebrities [34,72].…”
Section: Peer Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Organic cosmetics is a product category that has been growing rapidly, both globally and in Europe. Increased consumer interest in this product category is related to, among other factors, concern for the environment, widespread promotion of the concept of sustainable development, and interest in innovation in the cosmetics market (Klimczyk-Bryk 2000, Witek 2015, Nagarajan et al 2022.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…Improper planning of purchases and portions of food to be prepared; Nowadays, the concept of sustainable consumption is becoming more and more a major interest of the population and the latter make more conscious food purchasing decisions [15]. Indeed, increasing awareness towards environmental issues and climate change led society to the formation of sustainable consumption habits [16].…”
mentioning
confidence: 99%